2013
DOI: 10.1002/pts.2012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Private and Public Label Packaging on Consumer Purchase Patterns

Abstract: The evaluation of package branding is important to determine its ability to connect with consumers on an emotional level. In the past, focus groups have been the traditional method used to evaluate branding; however, focus groups can be seen as an inaccurate method of gathering data due to purely qualitative data collection. This paper presents a retail shopping experiment conducted in CUShop ™ , a consumer experience laboratory, to determine whether consumers prefer a public label product versus a private lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 14 publications
1
48
0
6
Order By: Relevance
“…Using ET to analyse the process of decision-making, researchers concluded that the purchase decision and the time spent observing the packaging indicates that participants preferred the packaging with widely recognised third-party brands compared to supermarket private label brands (Hurley, Ouzts, Fischer, & Gomes, 2013). Quantifying this interest through the visual attention given to one brand over a competing brand is another potential use of ET, since it would become a quantifiable parameter to analyse the impact of changes in the variables of BE boosters over time.…”
Section: Brand Equitymentioning
confidence: 99%
“…Using ET to analyse the process of decision-making, researchers concluded that the purchase decision and the time spent observing the packaging indicates that participants preferred the packaging with widely recognised third-party brands compared to supermarket private label brands (Hurley, Ouzts, Fischer, & Gomes, 2013). Quantifying this interest through the visual attention given to one brand over a competing brand is another potential use of ET, since it would become a quantifiable parameter to analyse the impact of changes in the variables of BE boosters over time.…”
Section: Brand Equitymentioning
confidence: 99%
“…Upon the completion of the pre-search exercise and the calibration of the eyetracking equipment (Hurley et al, 2013), the respondents started a trip planning exercise. They were instructed to plan and "purchase" a flight and hotel in Casablanca for two people within a specified period of time.…”
Section: Stage 2: Trip Planning Exercisementioning
confidence: 99%
“…Dessa forma, algumas informações podem não ser encontradas ou compreendidas pelo consumidor, gerando uma experiência negativa com o produto e consequentemente com a marca. Para Hurley et al (2013), embalagens bem projetadas podem ajudar o produto a superar a concorrência, entretanto, embalagens mal concebidas podem ter impacto negativo sobre a venda e a imagem da marca.…”
Section: Design De Embalagensunclassified